2011
DOI: 10.1155/2011/916380
|View full text |Cite
|
Sign up to set email alerts
|

Does Varicocelectomy Improve Gonadal Function in Men with Hypogonadism and Infertility? Analysis of a Prospective Study

Abstract: Varicocele in infertile males is associated with Leydig cell dysfunction and hypogonadism. The effect of varicocelectomy on serum testosterone level is not yet established. We analysed 200 heterosexual infertile men diagnosed to have clinical varicocele they were divided into two groups: group 1 (100 men) had microsurgical varicocelectomy, and group 2 (100 patients) underwent assisted reproduction procedures. All participants had semen analysis, serum levels of follicle-stimulating hormone (FSH), luteinizing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…A 2007 study by Lee et al [17] showed a postvaricocelectomy rise in testosterone compared to baseline, but the change did not reach statistical significance. This likely resulted from the relatively small numbers of individuals (12) and the very wide range of testosterone values recorded after varicocelectomy (416 AE 358 ng/dl).…”
Section: Key Pointsmentioning
confidence: 99%
“…A 2007 study by Lee et al [17] showed a postvaricocelectomy rise in testosterone compared to baseline, but the change did not reach statistical significance. This likely resulted from the relatively small numbers of individuals (12) and the very wide range of testosterone values recorded after varicocelectomy (416 AE 358 ng/dl).…”
Section: Key Pointsmentioning
confidence: 99%
“…Furthermore, it not only controls mechanical process of penile erection, but also the male sexual behaviour and attitudes (Corona & Maggi, 2010;Sathya Srini & Belur Veerachari, 2011). Testosterone plays an important role in sexual response and regulates the timing of the erectile process as a function of sexual desire, thereby coordinating penile erection with sex.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…It has been proven and accepted that surgical repair significantly increases testosterone levels in men with varicocele (Dabaja & Goldstein, 2016;Dabaja, Wosnitzer, & Goldstein, 2013;Hsiao et al, 2013;Hsiao et al, 2011;Li et al, 2012;Najari, Introna, & Paduch, 2016;Sathya Srini & Belur Veerachari, 2011;Zohdy, Ghazi, & Arafa, 2011) Similarly, Sathya Srini and Belur Veerachari (2011) reported a significant increase of testosterone in patients diagnosed as infertility with clinical varicocele after microsurgical varicocelectomy. Besides, the number of participants suffered from erectile dysfunction in the study group was 44 before surgery decreased to 31 after 12 months of follow-up, while there was an increase from 39 to 41 during the follow-up period in the control group.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a question of possible beneficial effect of varicocelectomy on preventing development of late onset of hypogonadal state [8]. Confirmation of that statement obviously will require lengthy longitudinal population study.…”
mentioning
confidence: 99%